Headhunting and the body in Iron Age Europe - Armit, Ian. (Cambridge ; New York : Cambridge University Press, 2012)
"This book examines the widespread evidence for the removal, curation, and display of the human head in Iron Age Europe"--
Machine generated contents note: 1. Detached fragments of humanity; 2. A remarkable spiritual continuity?; 3. Shamans on the march; 4. Pillars, heads, and corn; 5. Neither this world, nor the next; 6. From the dead to the living; 7. Gods and monsters; 8. Bodies of belief.
Includes bibliographical references (p. 227-254) and index.
Keywords: Headhunters -- Europe; Human body -- Symbolic aspects -- Europe; Human remains (Archaeology) -- Europe; Rites and ceremonies -- Europe; Violence -- Europe; Iron age -- Europe; SOCIAL SCIENCE / Archaeology; Europe -- Social life and customs; Europe -- Religious life and customs